The application of energy analysis on an educational steam power plant - Mohmad Jaat, Md. Norrizam (2005)
The performance of an educational steam power plant with rated output of20 kW was analyzed based on the first and second laws of thermodynamics. Experimental data was obtained from the educational steam power plant located at the Thermodynamics laboratory, Faculty of Engineering, Kolej Universiti Tun Hussein Onn (KUITTHO) which used diesel as a fuel. Experiments were carried out to evaluate the performance of the steam power plant. The energy and exergy balances were carried out on each of component of the power plant, excluding the feedwater pump. The energy interactions, the exergy losses and the efficiencies of each component based on the first and second law of thermodynamic were evaluated. The results of the analysis show that the performance of the plant is influenced by both the boiler pressure and the superheater temperature. It was found that, the thermal and exergy efficiencies of the plant are 8.9% and 5.2% respectively. The results also indicate that, the major source of exergy destruction occurred in the steam boiler followed by losses in the turbine and condenser. Theexergy losses in boiler are mainly due to the heat loss during the combustion process. Conversion of chemical energy to heat energy and heat transfer between the combustion gases and water are the other causes of destructions.